Primary School Teachers' Views on Teaching Critical Thinking - Yılmaz Özelçi, Serap (Revija za elementarno izobraževanje, 2023)
Abstract: The main purpose of the study is to examine the views of classroom teachers on the teaching of critical thinking. It is a qualitative study. The data are collected through a semi-structured interview form. 13 classroom teachers are the study group of the research. Descriptive and content analysis is also used in the analysis of the data. According to the findings, teachers believe that critical thinking is a teachable skill and they know how important their roles are in teaching this skill. However, teachers emphasized that skill training would not be possible without family support.